Tensions between Privacy and Targeted Advertising - Batista, Manuel (2023)
The problem of data privacy on the internet takes on a huge proportion, considering that personal databases are a source of economic value for companies, which gives rise to extensive discussion in ethical and legal terms. This article proposes an analysis of privacy, addressing the issue of Cookies, used to obtain personal information from users for targeted advertising, even if there is no user consent, or if this is compromised due to lack of information or understanding. The article questions whether the General Data Protection Regulation (GDPR) of the European Union (EU) is being violated through this increasingly common practice in the context of Digital Marketing. The methodology used was qualitative, descriptive and bibliographical, based on the law (GDPR) and on articles that deal with the subject